Investigation of Leakage Current in Micro M-I-M Structure Using Multilayer High-K Dielectric Materials with COMSOL Multiphysics - Ullah, Naqeeb; Huang, Lingling; Amirzada, Muhammad Rizwan; Ullah, Anayat; Haider, Muhammad Luqman; Ehsan, Muhammad Khurram; Khan, Yousuf (Elektronika ir Elektrotechnika, 2022)
Micro Metal-Insulator-Metal (M-I-M) capacitor structures are well-known passive components that have been broadly used in integrated circuits, Radio Frequency (RF) decoupling, Micro Electro Mechanical Systems (MEMS) sensors, and health monitoring systems. Thanks to its small dimensions, it can be easily integrated into microelectronics. With the acceleration of the scalling dawn of integrated circuits and systems, the size of the capacitor and other components must be reduced. It has become challenging to fabricate a micro M-I-M capacitor with low leakage current and high-capacity density since the leakage current and depletion effect are reported as the main factors of the gradual loss of electrical energy in the micro-M-I-M capacitor. Thus, minimizing the leakage current and the depletion effect became a new research trend. This paper presents a penta-layer high-K dielectric between the electrodes to reduce the leakage current in the micro-M-I-M capacitor. For this purpose, various dielectric materials were investigated. It was found that niobium pentaoxide (Nb2O5) and hafnium dioxide (HfO2) as penta-layer dielectric materials provide the lowest leakage current between the two electrodes. The recorded values of leakage current density are reduced to a mere 0.95 µAmps/mm2 from several µAmps/mm2 at the operating voltage of 1 V. The reported micro-M-I-M capacitor has potential application as an energy storage device.